Synthesis and characterization of four new unsymmetrical potentially pentadentate Schiff base ligands and related Zn(II) and Cd(II) complexes - Dehghani-Firouzabadi, Ahmad Ali; Motevaseliyan, Fahimeh (European Journal of Chemistry, 2014)
Two thioether diamines 2-(2-aminoethylthio)aniline and 2-(3-aminopropylthio)aniline have been prepared employing a new procedure by reaction of 2-aminothiophenol and N-(2-bromoethyl)phthalimide or N-(3-bromopropyl)phthalimide, respectively. Then two new potentially pentadentate (N2O2S) Schiff base ligands derived from direct condensation between two maintained diamines and 2-hydroxybenzaldehyde or 5-bromo-2-hydroxy benzaldehyde were synthesized. Also, Zn(II) and Cd(II) complexes of Schiff base ligands have been prepared. These compounds have been characterized by physico-chemical and spectroscopic methods.